2023
DOI: 10.1007/s00122-023-04481-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and validation of four stable QTL for adult-plant resistance to powdery mildew in Chinese wheat cultivar Bainong 64

Xiaowan Xu,
Daojie Sun,
Zhongqiu Ni
et al.

Abstract: Wheat powdery mildew, caused by Blumeria graminis f. sp tritici (Bgt), is a devastating fungal disease. Seedlings of Chinese winter wheat cultivar Bainong 64 are susceptible to Bgt but adult plants have maintained slow-mildewing resistance since it was released in 1996. A population of 171 recombinant inbred lines (RILs) developed from cross Jingshuang 16/Bainong 64 (JS16/BN64) was used to dissect genetic components of powdery mildew resistance. A genetic map comprising 5,383 polymorphic markers was constructe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The two wheat populations used in this study were YZ F 6 RILs and JB F 6 RILs, which had been reported in Li et al [ 30 ] and Xu et al [ 31 ], respectively. The parents and 193 progenies in the YZ population (denoted as YZ1 to YZ193) were planted at Beijing and Shijiazhuang (Hebei Province) in 2011–2012 cropping season, and Gaoyi (Hebei Province) and Xinxiang (Henan Province) in 2019–2020 cropping season [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two wheat populations used in this study were YZ F 6 RILs and JB F 6 RILs, which had been reported in Li et al [ 30 ] and Xu et al [ 31 ], respectively. The parents and 193 progenies in the YZ population (denoted as YZ1 to YZ193) were planted at Beijing and Shijiazhuang (Hebei Province) in 2011–2012 cropping season, and Gaoyi (Hebei Province) and Xinxiang (Henan Province) in 2019–2020 cropping season [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The parents and 193 progenies in the YZ population (denoted as YZ1 to YZ193) were planted at Beijing and Shijiazhuang (Hebei Province) in 2011–2012 cropping season, and Gaoyi (Hebei Province) and Xinxiang (Henan Province) in 2019–2020 cropping season [ 30 ]. The parents and 181 progenies in the JB population (denoted as JB1 to JB181) were planted at Beijing and Gaoyi (Hebei Province) in 2019–2020 cropping season [ 31 ]. The samples for genotyping were harvested in Gaoyi 2019–2020 cropping season for both populations.…”
Section: Methodsmentioning
confidence: 99%